Ecotourism Development Plan in the Russian North National Park: The features and recommendations - Andrey Yu. DANILOV; Dmitry A. TSAPUK (Zenodo, 2022)
The article describes the main technologies, principles and results of the development of an Ecotourism Development Plan in the Russian North National Park. The uniqueness of this protected area has been identified and justified – the equivalent value of natural and cultural heritage with greater significance of cultural heritage on its territory. The problems and limitations of ecotourism development in the national park are identified and ways of their solution are proposed that will allow achieving the main goal of the Plan – the transformation of the national park "Russian North" into an independent direction of ecotourism of international level. Originally published in https://ruservices.rgutspubl.org/index.php/1/article/view/27